PENERAPAN MODEL THINK, PAIR AND SHARE DALAM PEMBELAJARAN MENULIS TEKS PROSEDUR PADA SISWA KELAS VII SMP NEGERI 1 KARANGAMPEL TAHUN AJARAN 2024/2025 - Dino Apriana; Muji Zain Naufal; Fithry Muthmainnah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Language in general is a tool for communication owned by humans which comes from a system of sound symbols from the human mouth. Basic competencies are developed based on three things that are interrelated and mutually supportive in developing students' knowledge, understanding, and having the competence of listening, reading, speaking, and writing. The purpose of this study is to determine the application of the think, pair and share model in learning to write procedural texts for grade VII students of SMP Negeri 1 Karangampel in the 2024/2025 academic year. The methods used in this study are interviews and observations using a quantitative approach. The instruments used are observation sheets conducted by teachers on students, and interviews conducted by researchers with Indonesian Language Teachers at SMPN 1 Karangampel. The results of statistical calculations using the independent samples t-test, obtained t count of 3.874 and t table of 1.729. Statistical calculations using the independent samples t-test, obtained an average value in the experimental class of 72.75 which is greater than the average value in the control class of 66, indicating that H0 is rejected and H1 is accepted.